2016
DOI: 10.1016/j.bandc.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Post-error adjustments and ADHD symptoms in adults: The effect of laterality and state regulation

Abstract: Evidence is accumulating that individuals with Attention-Deficit/Hyperactivity Disorder (ADHD) do not adjust their responses after committing errors. Post-error response adjustments are taken to reflect, among others, error monitoring that is essential for learning, flexible behavioural adaptation, and achieving future goals. Many behavioural studies have suggested that atypical lateral brain functions and difficulties in allocating effort to protect performance against stressors (i.e., state regulation) are k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 90 publications
0
13
0
Order By: Relevance
“…Alternatively, our RT data is in line with another response strategy; wherein, participants set a deadline for themselves to give an appropriate motor response. Here, once this deadline is passed they might give careless (and likely incorrect) responses (Mohamed et al 2016). PES, in this case, may reflect an extended deadline to increase the time needed for thoughtful information processing and consequently more accurate responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, our RT data is in line with another response strategy; wherein, participants set a deadline for themselves to give an appropriate motor response. Here, once this deadline is passed they might give careless (and likely incorrect) responses (Mohamed et al 2016). PES, in this case, may reflect an extended deadline to increase the time needed for thoughtful information processing and consequently more accurate responses.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were given a lexical decision task used in our previous work (see Mohamed et al 2016). The task was designed using E-prime software version 2.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the RT findings, the fact that responses were speeded prior to and during errors across groups indicates that RT dynamics were likely shaped by a speed-accuracy trade-off (Dudschig and Jentzsch, 2009), as described in the “Introduction” section, that is, errors can be thought of as premature, hasty responses (Scheffers and Coles, 2000), rather than resulting from decision uncertainty and subsequent guessing, which would result in slowed error responses, as predicted by the so-called deadline model (Ruthruff, 1996; Mohamed et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] Functional imaging studies have confirmed alterations in the action-monitoring network of unmedicated patients with ADHD, with reduced activation in medial and lateral prefrontal areas on error trials. 27,28 Moreover, in a behavioural study, Yordanova and colleagues 29 found that adolescents with ADHD showed increased behavioural instability in trials following incorrect responses ("post-error trials"), with respect to increased error rates and reaction time (RT) variability, indicating difficulties with the behavioural adjustments usually initiated after response errors (see also Wiersema and colleagues, 25 Schachar and colleagues 30 and Mohamed and colleagues 31 ). However, the neurobiological correlates underlying this altered posterror behaviour have rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%